Reviewed Study on Concept and Applied Properties of Fuzzy Set Theory: Exploring the Concepts and Applications of Fuzzy Set Theory for Decision Making (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Fuzzy Set Properties is the most embraced technique to deal with the imprecision. Aggregation and combination of information are significant issues in different fields of example acknowledgment, image processing and decision making. Making decisions is without a doubt a standout amongst the most basic exercises of individuals. The goal of fuzzy decision is to get a decision that is optimum.